2021
DOI: 10.1061/(asce)ae.1943-5568.0000444
|View full text |Cite
|
Sign up to set email alerts
|

Integrating BIM in Higher Education Programs: Barriers and Remedial Solutions in Australia

Abstract: Despite the increasingly widespread adoption of Building Information Modelling (BIM) in Australia, a steady pipeline of BIM-ready graduates needed to meet industry demand remains elusive. Anecdotal evidence suggests that universities in Australia have not been successful in delivering BIM-enabled graduates of the right calibre due to a plethora of barriers. This paper aims to identify, define and delineate barriers to integrating BIM education into programs in Australian higher education institutions (HEIs), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Clevenger et al [ 19 ] studied the way to integrate BIM technology into architectural engineering-related courses. Casasayas et al [ 20 ] divided reasons that hinder BIM education in Australian universities into four aspects: change management adjustment, curriculum and content restrictions, problems of educators, and disconnection from the industry. Through the research, they pointed out that researchers should provide the link between graduates’ preparation for BIM and their employability in the Australian market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clevenger et al [ 19 ] studied the way to integrate BIM technology into architectural engineering-related courses. Casasayas et al [ 20 ] divided reasons that hinder BIM education in Australian universities into four aspects: change management adjustment, curriculum and content restrictions, problems of educators, and disconnection from the industry. Through the research, they pointed out that researchers should provide the link between graduates’ preparation for BIM and their employability in the Australian market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rapid development of BIM creates a high demand for experienced BIM professionals in the construction industry market. However, many countries have had a shortage of BIM personnel for years [9,14,15]. To meet the industry demand, educational institutions have introduced BIM-related training programs in different modes such as higher education, on-job training, vocational training or professional training [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To meet the industry demand, educational institutions have introduced BIM-related training programs in different modes such as higher education, on-job training, vocational training or professional training [10]. Many researchers reported that BIM education is much more than instructions of software package usage; the more important is introducing the consistency in BIM approach and collaboration between all disciplines involved in a construction project [15,1]. It is not only about the new system and tools; it is about how people involved can together use the tools and systems efficiently to achieve the common goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BIM educational programs start with creating awareness and educating students and trainees on how to use different industry-specific BIM software packages (e.g., Revit, ArchiCAD, Navisworks, Rhino3D, Aconex, etc.) for modelling, viewing, simulating, scheduling, or data sharing (see [10][11][12][13][14][15][16]). Courses often begin by highlighting the benefits and barriers of BIM, including the reasons for BIM adoption in the AEC-FM industry (e.g., [17][18][19][20][21][22][23][24][25][26][27]) and the progress on BIM knowledge and authoring/manipulation skills (e.g., [28][29][30][31]).…”
Section: Introductionmentioning
confidence: 99%